Mia the bridesmaid fairy - Meadows, Daisy (New York : Scholastic, 2010)
When Jack Frost steals three magic tokens from Mia the bridesmaid fairy, Rachel and Kirsty try to help her recover the tokens before Kirsty's cousin's wedding is ruined.
Originally published: London : Orchard Books, 2009.
Keywords: Fairies -- Fiction; Magic -- Fiction; Bridesmaids -- Fiction; Weddings -- Fiction